2017
DOI: 10.1002/chem.201702917
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Ultrasmall Fluorinated Graphene with High NIR Absorbance for Controlled Delivery of Mixed Anticancer Drugs

Abstract: Fluorinated graphene (FG) possess distinctively novel properties different from graphene and is suitable for many biomedical applications. However, the hydrophobic nature and inert properties of FG limit its further application as a biological material. Here we show the preparation of nano-sized FG (ca. 60 nm) that exhibits high NIR absorbance for photothermal therapy. In order to make it stable in physiological solutions, the FG is enriched with oxygen and followed by covalent binding with chitosan as a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…S3). This was mostly because that after PEG-FA modification, the long chain of PEG made the hydration degree become stronger and thus the DLS size was larger, similar to previous work [53,54]. And such a small size considerably enhanced the cell uptake by endocytosis [37].…”
Section: Materials Advances Accepted Manuscriptsupporting
confidence: 68%
“…S3). This was mostly because that after PEG-FA modification, the long chain of PEG made the hydration degree become stronger and thus the DLS size was larger, similar to previous work [53,54]. And such a small size considerably enhanced the cell uptake by endocytosis [37].…”
Section: Materials Advances Accepted Manuscriptsupporting
confidence: 68%
“…Signicant efforts are currently directed at the development of nanocarriers to solve the problems of low drug solubility in blood and under unfavourable pharmacokinetic conditions (rapid release), as in the case of CPT. In this context, nanomaterials can effectively transport these molecules to cancer cells, facilitating their delivery and intracellular uptake, 18 prolonging their release time and optimizing their distribution in the body. In addition, these molecular carriers can be developed as high-capacity platforms for encapsulating antitumor drugs, [19][20][21] an important property for optimizing the amount of antitumor drugs within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…At 7 μg mL −1 , treatment with GO‐CO‐ γ ‐PGA‐DOX resulted in a stronger signal (89415) than those of free DOX (87343), GO‐DOX (57177) and GO‐CO‐DOX (82241) in cells. These results revealed that the GO‐CO‐ γ ‐PGA composite is an efficient carrier for taking DOX into cells and releasing drugs to perform their function …”
Section: Resultsmentioning
confidence: 99%